Andragogical and pedagogical methods for curriculum and program development (Advances in educational tehcnologies and instructional design (AETID) book series., 2014)
"This book offers an in-depth description of key terms and concepts related to curriculum and program development for both faculty and students, as well as program designers, instructional program developers, trainers, and librarians"--Provided by publisher.